(untitled) (Research, Society and Development, 2021)
Suicide is a public health problem that persists today around the world. This study aimed to describe the profile of suicide cases in the state of Ceará. A quantitative and descriptive approach was used, data collection was performed on the DATASUS website, in the time frame from 2012 to 2019, in the vital statistics of the groups of the databases of the Mortality Information System 1996 to 2015, by the ICD-10 and preliminary data from 2016 the sociodemographic data and the means used death of deaths by suicide in the State of Ceará, as well as the population estimates of the Brazilian Institute of Geography and Statistics. The data were analyzed according to descriptive statistics, being based on research of Brazilian regions and cities, with critical analysis of the data. The results showed, in the period between 2012 and 2017, 3,393 deaths by suicide in Ceará, with the mortality rate per 100,000 inhabitants. The distribution of deaths caused by suicide showed a prevalence in males, in individuals aged between 30 and 39 years, with a level of education ranging from 4 to 7 years old, single, brown individuals with the main place of occurrence the household. Thus, mental health actions are needed in health promotion, disease prevention and monitoring of people at risk for suicide, strategies that reinforce the awareness and empowerment of professionals through continuing education in health services and civil society, especially with regard to the stigmatized perspective.